Комунікаційна та інформаційна політика при формуванні іміджу вищих навчальних закладів - Педченко, Анна Павлівна; Педченко, Анна Павловна; Pedchenko, Anna; Власюк, Юлія Олександрівна; Власюк, Юлия Александровна; Vlasiuk, Yuliia (ПДАТУ, 2015)
UK: Сформульовані сутність та основні напрями комунікаційної політики, названі шляхи підвищення впізнаваності вищих навчальних закладів. Визначені основні цілі, стратегічні та тактичні завдання інформаційної політики вишів, а також суб’єкти та функції управління інформаційними потоками в контексті формування і управління іміджем та підвищення конкурентоспроможності вишів на ринку освітніх послуг. EN: The strategic goal in the context of competitiveness of higher education institutions involves, the formation and management of university image including. This distant result for obtaining of which a great role has been belongs to the communications and information policy. In the article the components of the communication and information policy of higher education institutions for the universities image formation and management and their competitiveness rising on the educational services market is determined. Communication policy is considered as a course of action for university aimed at the planning and implementation of cooperation the institution with every subjects of marketing system based on the use a means of communication that provide stable and effective demand formation and educational and scientific services promotion for satisfaction of existing needs in society. Information policy in higher education institution regarded as planned activities to ensure information flows in the media for realization of strategic goal, which is the information space conquest. The implementation of these problems requires the development of a the program complex that should take shape in concrete directions of activities of higher education institutions, and start of their implementation should be the point of reference for estimation of the success of communications and information policy of the institution. Thus realization of action programs on these directions will increase the university authority, and allows to enhance competitiveness of it on the educational services market, to build new and to strengthen existing relationships with enterprises and organizations of the real economy sectors. RU: Сформулированы сущность и основные направления коммуникационной политики, названы пути повышения узнаваемости высших учебных заведений. Определены основные цели, стратегические и тактические задачи информационной политики вузов, а также субъекты и функции управления информационными потоками в контексте формирования и управления имиджем, повышения конкурентоспособности вузов на рынке образовательных услуг.
The communication and information policy for university image forming
Keywords: вищий навчальний заклад; імідж; комунікаційна політика; інформаційна політика; высшее учебное заведение; имидж; коммуникационная политика; информационная политика; higher education institutions; image; communication policy; information policy